Repeated mild traumatic brain injury induces persistent variations in mitochondrial DNA copy number in mesocorticolimbic neurocircuitry of the rat. (June 2020) - Balasubramanian, Nagalakshmi; Srivastava, Abhinav; Pawar, Namrata; Sagarkar, Sneha; Sakharkar, Amul J.
Highlights: Mitochondrial DNA copy number (mtDNAcn) varied in different brain regions. Repeated mild traumatic brain injury (rMTBI) induced persistent changes in mtDNAcn. The 16S rRNA levels were concomitantly changed with respect to mtDNAcn variations. Abstract: Mild traumatic brain injury (MTBI) results in persistent deficits in the cognitive and emotive abilities governed by the mesocorticolimbic (MCL) neurocircuitry. In this study, we observed regional variations in the mitochondrial DNA copy number (mtDNAcn) in the MCL neurocircuitry. Although repeated MTBI (rMTBI) is known to cause mitochondrial dysfunction, the persistent changes in the mtDNAcn and its manifestations in 16S rRNA levels in the MCL neurocircuitry have not been investigated. Herein, we employed the closed head weight drop paradigm to induce rMTBI in rats. We analyzed the mtDNAcn and 16S rRNA levels in eight regions of the MCL neurocircuitry 48 h and 30 days after the rMTBI. The mtDNAcn in the prefrontal cortex, cortex, hippocampus, and ventral tegmental area (VTA) of the rMTBI-exposed rats was decreased at both the time points. Although the mtDNAcn was reduced in hypothalamus and amygdala at 48 h, it was increased at 30 days post rMTBI. The 16S rRNA levels and mtDNAcn were altered in all the regions, with the exception of bed nucleus of stria terminalis and the VTA. Moreover, the rMTBI did not affect the mtDNAcn and 16S rRNA levels in nucleus accumbens. These results suggest that the repetitive trauma induces persistent changes in the mtDNAcn which are manifested as aberrations in mitochondrial transcription in the brain areas crucial for emotion and cognition.